PERSEPSI SISWA SMK AZ ZAHRA MLONGGO JEPARA TENTANG ASPEK PORNOGRAFI DALAM FILM DILAN 1991 - Khoirul Muslimin (An-Nida : Jurnal Komunikasi Islam, 2021)
The film Dilan 1991 is a sequel to the previous film Dilan 1990 with the highest number of viewers in 2019. This teen romance drama genre film was adopted from the novel entitled Dilan: Dia is Dilanku in 1991 by Pidi Baiq. This romance nuanced film makes pornographic elements very thick in it. This study was conducted to find out how the students of SMK Az Zahra Mlonggo's perception of the pornographic aspect of the 1991 film Dilan. This study used a qualitative method with a focus group discussion approach. Then analyzed using content analysis method. The data validity technique was carried out using a source triangulation technique with attribution theory by Fritz Haider. From the results of student perceptions, it shows that there are pornographic aspects in the 1991 film Dilan including action porn, sound porn and pornography. Student perceptions are divided into two, namely positive perceptions and negative perceptions. Positive perception is a natural, normal, and mediocre thing because it is influenced by association, knowledge, insight, needs, pleasures and student habits. Negative perception, an impression is not good because students judge from a religious point of view